Anthropological Study of the Rejang Dewa Dance in Sedahan Jaya Village, Sukadana District, North Kayong Regency - Septiani, Dwi; Aditya, Mega Cantik Putri; Satrianingsih, Aline Rizky Oktaviari (Universitas Tanjungpura, 2024)
This research was conducted to understand the Anthropological Study of the Rejang Dewa Dance in Sedahan Jaya Village, Sukadana District, North Kayong Regency. The method used was descriptive method with a qualitative research design. The approach employed was anthropological and ethnographic approach. Data sources were obtained through informants knowledgeable about the anthropological study of the Rejang Dewa Dance in Sedahan Jaya Village, Sukadana District, North Kayong Regency. The research data consisted of anthropological studies of the Rejang Dewa Dance and the distinctive characteristics of the Rejang Dewa Dance. Data collection techniques included interview techniques, observation techniques, and documentation techniques. Data validity testing techniques used triangulation and extended observation. The results of the study are: (1) the anthropological study of the Rejang Dewa Dance in Sedahan Jaya Village originated from the transmigration of Hindu-Balinese communities due to the eruption of Mount Agung in 1963. (2) the distinctive characteristic of the Rejang Dewa Dance in Sedahan Jaya Village, Sukadana District, North Kayong Regency is that the dancers are females who are still pure or have not yet menstruated and can only be performed in the temple.